On the Faintly $e$-Continuous Functions - Caldas, Miguel (Sarajevo Journal of Mathematics, 2024)
A new class of functions, called faintly $e$-continuous functions, has been defined and studied. Relationships among faintly $e$- continuous functions and $e$-connected spaces, $e$-normal spaces and $e$-compact spaces are investigated. Furthermore, the relationships between faintly $e$-continuous functions and graphs are investigated. 2000 Mathematics Subject Classification. 54B05, 54C08, 54D10